MANAGEMENT OF SHEA PARKLANDS IN THE WEST AFRICAN SAVANNAH - Shu-aib Jakpa, S.; Lovett, J. C.; Donkoh, S. A. (UDS International Journal of Development, 2018)
This research was conducted in Ghana to identify the strategies and practices used in managing shea trees. A multi-stage sampling design was used to select 540 farmers for the study. Descriptive statistics were used to analyze the relationships between socio-demographic factors and willingness to continue managing shea trees. Even though almost all the respondents expressed willingness to continue managing the shea trees, the most willing included the following: natives; those who purchased their lands; farmers with shea trees closer to their homes; those who owned their lands in addition to the shea trees and communities where the landlords or the community as a whole had authority over the lands and shea trees. The use of alternative sources of energy such as gas stoves, solar panels and locally-made stoves with high energy-use efficiency should be encouraged and made readily available and affordable to reduce dependence on shea trees as sources of energy for cooking and heating. Farmers should also be encouraged to grow fast-growing tree species such as Luecaena leucocephala, Senna siamea, Gliricidia sepium and Albizzia lebbeck as woodlots to serve as alternative sources of fuelwood and fodder. Furthermore, for their willingness to conserve the trees, farmers should be compensated for carbon credits generated from their shea parklands. Keywords: Shea Trees, Management Practices, Willingness to Manage, Northern Ghana